Connell's Persona, Shadow, and Anima in Sally Rooney's Normal People - Alisyah Nur Rahma (Journal of Language, Literature and Teaching, 2026)
This study examines the manifestation of Carl Jung’s archetypes of Persona, Shadow, and Anima in the character of Connell Waldron in Sally Rooney’s Normal People (2018), as well as how his individuation process unfolds through his evolving relationship with these three archetypes. The objectives of this study are to identify how the Persona, Shadow, and Anima manifest in Connell’s character and to examine the progression of his individuation through the integration of these archetypes. This research employs psychoanalytic literary criticism grounded in Jungian theory, using a descriptive qualitative method. The primary data consist of dialogues, internal monologues, and narrative descriptions taken from the novel, while the secondary data are drawn from relevant theoretical and academic sources. The findings reveal that Connell’s Persona manifests through two social roles, the popular student and the loyal friend. Beneath these masks, his Shadow consists of repressed insecurity rooted in class difference, internalized shame, and guilt over the death of his friend, Rob. Meanwhile, his Anima emerges through the vulnerability and tenderness that surface only within his relationship with Marianne Sheridan. Connell’s individuation unfolds gradually across three stages: he confronts his Persona at university by reconnecting with his authentic self through literature, integrates his Shadow by consciously choosing therapy and medication, and integrates his Anima by transforming sporadic emotional outbursts into a conscious form of care for Marianne. This study concludes that Rooney portrays individuation not as a sudden transformation, but as a quiet and ongoing process shaped by deliberate choices and the presence of meaningful relationships.